Hemiazygos-accessory hemiazygos continuation of left-sided inferior vena cava: A case report and review of the literature - Nedasadat Rezaei; Manizhe Ataee Kachuee; Peyman Famili; Ghazaleh Salehabadi (Radiology Case Reports)
Left side transposition of the inferior vena cava (IVC) is a rare anatomical variation formed during its complex embryonic developmental process. We present a 71-year-old female patient with an incidentally identified left-sided IVC in contrast-enhanced computed tomography during gastrointestinal bleeding workup. The left-sided IVC formed a hemiazygos-accessory hemiazygos continuation. A narrowing of the right retroaortic renal vein, consistent with the nutcracker phenomenon, was observed. Left-sided IVC, although asymptomatic in the majority of cases, may act as source of diagnostic confusion or contribute to deep vein thrombosis of lower extremities, especially in younger patients. Care must be practiced to establish a comprehensive diagnosis and minimize procedural risks.